2019
DOI: 10.1371/journal.pone.0215831
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo half-life extended prolactin receptor antagonist can prevent STAT5 phosphorylation

Abstract: Increasing evidence suggests that signaling through the prolactin/prolactin receptor axis is important for stimulation the growth of many cancers including glioblastoma multiforme, breast and ovarian carcinoma. Efficient inhibitors of signaling have previously been developed but their applicability as cancer drugs is limited by the short in vivo half-life. In this study, we show that a fusion protein, consisting of the prolactin receptor antagonist PrlRA and an albumin binding domain for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Our previous study in glioblastoma demonstrated increased PRLR expression levels and indicated some efficacy to reduce tumor cell growth by using PRLRA in experimental systems [39]. These data support the idea that the PRL system is relevant in tumorigenesis and that agents blocking the receptor or drugs conjugated with PRLRA may be of relevance for future pharmaceutical development [60].…”
Section: Discussionsupporting
confidence: 65%
“…Our previous study in glioblastoma demonstrated increased PRLR expression levels and indicated some efficacy to reduce tumor cell growth by using PRLRA in experimental systems [39]. These data support the idea that the PRL system is relevant in tumorigenesis and that agents blocking the receptor or drugs conjugated with PRLRA may be of relevance for future pharmaceutical development [60].…”
Section: Discussionsupporting
confidence: 65%
“…STAT5 pathway, which is the canonical pathway for long PRLR signalling 31 , was reported to be over-activated in GBM and directly involved in the modulation of proliferation, cellular transformation, migration and apoptosis 3234 . Blockade of PRLR using different antagonists in GBM cells efficiently inhibited the phosphorylation of STAT5 12,35 . PRL was also reported to stimulate Ca 2+ entry and its intracellular mobilization in GBM cells, together with a dose-dependent increase of GBM cell proliferation and viability 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human prolactin antagonists are potential drugs that inhibit target prolactin receptors in dopamine-resistant prolactinomas, breast cancer, prostate cancer, and ovary cancer, in all cases where autocrine PRL acts as growth promoting agent, or even for pain release and to avoid hair loss (O'Sullivan and Bates 2016 ). There are several PRLR antagonists reported in the literature (Goffin 2017 ; Tallet et al 2008 ) that downregulate the proliferation of a variety of cells expressing prolactin receptors: G129R-hPRL (Chen et al 1999 ), S179D-hPRL (Chen et al 1998 ), Δ 1-9- G129R-hPRL and Δ 1-14 -G129R-hPRL (Bernichtein et al 2003a , b , c ), Δ 1-9 -C11S-S33A-Q73L-G129R-K190R-hPRL (Yu et al 2019 ) and also G120R-hGH (Menezes et al 2017 ). All prolactin antagonists have been up to now synthesized as inclusion bodies in the cytoplasm of E. coli (Chen et al 1998 ; Oclon et al 2018 ; Yu et al 2019 ), or secreted into the medium by transfected CHO cells (Soares et al 2006 ; Swiech et al 2012 ) or mouse L-cells (Chen et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several PRLR antagonists reported in the literature (Goffin 2017 ; Tallet et al 2008 ) that downregulate the proliferation of a variety of cells expressing prolactin receptors: G129R-hPRL (Chen et al 1999 ), S179D-hPRL (Chen et al 1998 ), Δ 1-9- G129R-hPRL and Δ 1-14 -G129R-hPRL (Bernichtein et al 2003a , b , c ), Δ 1-9 -C11S-S33A-Q73L-G129R-K190R-hPRL (Yu et al 2019 ) and also G120R-hGH (Menezes et al 2017 ). All prolactin antagonists have been up to now synthesized as inclusion bodies in the cytoplasm of E. coli (Chen et al 1998 ; Oclon et al 2018 ; Yu et al 2019 ), or secreted into the medium by transfected CHO cells (Soares et al 2006 ; Swiech et al 2012 ) or mouse L-cells (Chen et al 1998 ). Periplasmic expression of recombinant proteins in E. coli has been considered to be a valid option for obtaining a soluble and correctly folded protein, as an alternative to the cytoplasmic production, in inclusion bodies, of an unfolded, insoluble protein carrying an extra initial methionine (Dalmora et al 1997 ; Dias et al 2018 ; Menezes et al 2017 ; Morganti et al 1998 ; Sockolosky and Szoka 2013 ; Suzuki et al 2012 ; Taherian et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%